(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
The roles of Short Rotation Coppice (SRC) Technology in fuelwood supply and offsetting CO2 emissions in the Tanzania and most African countries remain poorly understood. This study was carried in Rungwe District, Mbeya region in Tanzania, to determine trends, extent and drivers of adoption of SRC; identify various sources of household energy and assess the contribution of SRC to the total household fuelwood needs, and trees and shrub species used as sources of fuelwood. Data were collected using reconnaissance, field and social surveys and was analyzed using the Statistical Package for Social Sciences (SPSS). Results revealed that, 97.5% of local community adopted the SRC technology since 1960s. Eucalyptus spp. are mostly planted in woodlots and field boundaries while Persea americana and Leucaena leucocephala are intercropped in farmlands. The survey indicated that out of 176 tons of fuelwood used annually, 73% comes from SRC technology, 25% from non-SRC technology, and only 2% is purchased to supplement household fuelwood shortage. Local communities depend heavily on biomass energy from woodlots and farmlands where tree species like Eucalyptus spp. plays a key role in meeting the energy demand. This study demonstrates that SRC technologies like woodlots, boundary planting, and intercropping in farmland hold high promise to meet the household energy demand. If promoted and backed with strong policies and supportive land tenure, these technologies may reduce the harvesting pressure on native forests for energy demand and contribute to climate change mitigation and adaptation. Int. J. Agril. Res. Innov. & Tech. 6 (1): 41-46, June, 2016